2016
DOI: 10.1161/strokeaha.116.013766
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Antiepileptics and Seizure Incidence Following Subarachnoid Hemorrhage

Abstract: Background and Purpose The utility of prophylactic antiepileptic drug (AED) administration following spontaneous subarachnoid hemorrhage (SAH) remains controversial. AEDs have not clearly been associated with a reduction in seizure incidence and have been associated with both neurologic worsening and delayed functional recovery in this setting. Methods We retrospectively analyzed a prospectively collected database of SAH patients admitted to our institution between 2005 and 2010. Between 2005 and 2007, all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 26 publications
0
28
1
2
Order By: Relevance
“…These factors affect both electrophysiology and the likelihood of seizures. Previous prospective studies have found mixed results regarding the efficacy of antiseizure drug(ASD) prophylaxi . The mixed results of these studies suggest that ASD prophylaxis likely has a modest, if any, effect on both the suppression of cortical irritability and seizure risk.…”
Section: Discussionmentioning
confidence: 99%
“…These factors affect both electrophysiology and the likelihood of seizures. Previous prospective studies have found mixed results regarding the efficacy of antiseizure drug(ASD) prophylaxi . The mixed results of these studies suggest that ASD prophylaxis likely has a modest, if any, effect on both the suppression of cortical irritability and seizure risk.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis will require a high index of suspicion and performance of an EEG. Routine seizure prophylaxis with AEDs remains controversial as there is a lack of demonstrable benefit [16] [17].…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent efforts to introduce a guideline for seizure prophylaxis in SAH patients, a consensus regarding a uniform protocol for all of these patients has not been achieved. Several authors have questioned the benefits of seizure prophylaxis for all patients and many others believe that they can only prevent late seizures in patients with certain risk factors (3,25). Different seizure prophylaxis regimens are used in neuro-vascular units, primarily based on experience with certain medication and the dosage and duration of prophylaxis are determined according to patients' drug history, past medical history of central nervous system lesions, the occurrence of seizures, drug interactions, and side effect profile.…”
Section: Discussionmentioning
confidence: 99%